100 GHz Reflectometer for Sensitivity Analysis of MEMS Sensors Comprising an Intermediate Frequency Six-port Receiver - Linz, Sarah; Oesterle, Florian; Talai, Armin; Lindner, Stefan; Mann, Sebastian; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (IEEE Topical Conference on Wireless Sensors and Sensor Networks, 2015)
Due to the growing market for Micro Electro Mechanical Systems (MEMS), especially for the application in mobile electronic devices like cameras, phones or tablet computers, cost and time efficient test and evaluation systems are required for the production process. This work presents a novel measurement setup for MEMS microphones, that allows an inline, contactless evaluation of the microphones' mechanical sensitivity at an early stage of the manufacturing process. A heterodyne receiver with a Six-port demodulator is deployed for displacement detection with micrometer resolution. Since the Six-port demodulator allows very high sampling rates only limited by the analog-to-digital converter, short measurement times can be achieved.
elib2cris::1512001600,linz2015
Keywords: MEMS; Six-Port; Microwave Interferometer; W-band; Contactless Testing; Pull-in; Mechanical Sensitivity

24 GHz Six-Port Medical Radar for Contactless Respiration Detection and Heartbeat Monitoring - Vinci, Gabor; Lindner, Stefan; Barbon, Francesco; Hofmann, Maximilian; Fischer, Georg; Kissinger, Dietmar; Kölpin, Alexander (9th European Radar Conference, 2012)
For numerous medical applications it is of primary interest to monitor the breath rate and heartbeat of a patient over time. Especially important is to observe the respiration of a patient over night to detect potential sleep disorders. Furthermore, heartbeat frequency is also a precious informationwhich can help to improve diverse diagnosis procedures. In orderto better analyze these vital parameters an innovative contactlessrespiration detection and heartbeat monitoring technique hasbeen developed. This novel method is based on the six-portinterferometric radar and is capable of detecting breath rateas well as heartbeat frequency without applying sensors orelectrodes on the patients body.
elib2cris::1512001600,vinci2012f
Keywords: Six-Port; Bioradar; Vital Sign Monitoring; Heartbeat Detection; Respiration Detection

61 GHz Millimeter Wave Voltage Variable Attenuator Based on Flip-Chip Mounted PIN-Diodes - Mann, Sebastian; Lurz, Fabian; Lindner, Stefan; Barbon, Francesco; Linz, Sarah; Weigel, Robert; Kölpin, Alexander (20th International Conference on Microwaves, Radar, and Wireless Communications, 2014)
Voltage Variable Attenuators play a major role in radio frequency system design. In this paper, a voltage variable attenuator concept suitable for the 61GHz ISM band is introduced and discussed. The proposed reflection type voltage variable attenuator has a maximum attenuation of 32 dB in the 61 GHz ISM-band range, and a low phase-shift of less than 10° for low and medium attenuation values. Furthermore, a bias network is presented featuring low reflection loss, and robustness against manufacturing tolerances. For verification purposes, a voltage variable attenuator as well as a reference transmission line have been fabricated and measured.
elib2cris::1512001600,mann2014b
Keywords: 61 GHz; attenuator; bias network; p-i-n diode; reflection type; variable attenuator

61 GHz Six-Port Radar Frontend for High Accuracy Range Detection Applications - Mann, Sebastian; Vinci, Gabor; Lindner, Stefan; Linz, Sarah; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (IEEE-APS Topical Conference on Antennas and Propagation in Wireless Communications, 2013)
Abstract — Range detection is an challenging task, especially if high accuracy has to be reached. The hereby proposed 61GHz continuous wave radar system is based on a phase detector using Six-Port technique. For accuracy enhancement an improved isolation radar coupler has been introduced for broadband frequency modulated continuous wave radar as well as narrow band radar techniques. Furthermore, a Six-Port network based on four hybrid couplers is presented. Finally, the most important system subcomponents have been validated by measurements.
elib2cris::1512001600,mann2013a
Keywords: Six-Port; Radar Coupler

A 77 GHz Direction of Arrival Detector System with SiGe Integrated Six-Port Receiver - Vinci, Gabor; Lämmle, Benjamin; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (Radio-Wireless Symposium, 2012)
In this publication the design of a 77 GHz Direction-Of-Arrival (DOA) detector system with an Integrated SiGe six-port receiver and a passive microstrip antenna network is presented. The introduction of the six-port receiver for industrial sensors and automotive radar applications has opened a whole new set of possibilities and implementations. A typical problem though of Millimeter-Wave (MW) integration is the interface between the on-chip circuitry and the off-chip system electronics or passives. The antenna design aspects and interconnections are presented with a layouting analysis as well as a system overview of the DOA detector for a flexible, low-complexity and low-cost solution in microstrip technology.
elib2cris::1512001600,vinci2012a
Keywords: Antenna measurements; Antennas; Automotive engineering; Detectors; Microstrip; Radar; Receivers

A Compact, Versatile Six-Port Radar Module for Industrial and Medical Applications - Linz, Sarah; Vinci, Gabor; Mann, Sebastian; Lindner, Stefan; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (Journal of Electrical and Computer Engineering, 2013)
The Six-port receiver has been intensively investigated in the last decade to be implemented as an alternative radar architecture. Plenty of current scientific publications demonstrate the effectiveness and versatility of the Six-port radar for special industrial, automotive and medical applications, ranging from accurate contactless vibration analysis, through automotive radar calibration to remote breath and heartbeat monitoring. Its highlights, such as excellent phase discrimination, trivial signal processing, low circuit complexity and cost have lately drawn the attention of companies working with radar technology. A joint project involving the University of Erlangen-Nuremberg and InnoSenT GmbH (Innovative Sensor Technology), led to the development of a highly accurate, compact and versatile Six-port radar module aiming at a reliable high-integration of all subcomponents such as antenna, Six-port front-end, baseband circuitry and digital signal processing in one single package. Innovative aspects in the RF front-end design as well as in the integration strategy are hereby presented, together with a system overview and measurement results.
elib2cris::1512001600,linz2013b

A Compact, Versatile Six-Port Radar Sensor for Industrial and Medical Applications - Linz, Sarah; Vinci, Gabor; Lindner, Stefan; Mann, Sebastian; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (IEEE Sensors, 2013)
The Six-Port receiver can be implemented as an alternative radar architecture. Plenty of current scientific publications demonstrate the effectiveness and versatility of the Six-Port radar for industrial, automotive and medical applications: accurate contactless vibration analysis, distance measurements as well as remote breath and heartbeat monitoring. Its highlights are excellent phase discrimination, trivial signal processing, low circuit complexity and cost. A joint project involving the University of Erlangen-Nuremberg and InnoSenT GmbH led to the development of iSYS-5001, a compact, versatile Six-Port radar module aiming at a reliable high-integration of all subcomponents in one single sensor unit.
elib2cris::1512001600,linz2013a

ADC Depending Limitations for Six-Port Based Distance Measurement Systems - Lindner, Stefan; Barbon, Francesco; Linz, Sarah; Lurz, Fabian; Mann, Sebastian; Weigel, Robert; Kölpin, Alexander (IEEE Topical Conference on Wireless Sensors and Sensor Networks (WiSNet), 2015)
This publication will show some considerations for selecting an appropriate analog-digital-converter (ADC) in Six-Port based radar systems for distance measurements. It will be discussed how the ADC resolution is limiting the overall system range resolution. Furthermore, configurations with non-synchronous sampling of the four baseband signals and their influences on the system performance will be investigated.
elib2cris::1512001600,lindner2015
Keywords: distance measurement; low-cost; radar; six-port; synchronous sampling; adc

A high accuracy Direction-Of-Arrival and Misalignment Angle Detector - Vinci, Gabor; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (German Microwave Conference, 2011)
High-precision Direction-Of-Arrival measurements are often a challenge. The need to accurately detect the angle of incidence of an incoming electromagnetic wave with respect to a reference geometrical axis is very important for automotive and security applications. Furthermore, the ability to measure a misalignment angle of a transmitting antenna in respect to a reference is a task required by countless industrial applications. A high accuracy angle-detection system is hereby presented and measurement results from a prototype detecting a 24 GHz source are shown.
elib2cris::1512001600,vinci2011

A Low-Cost 2.4 GHz Frequency Measurement System for Microsecond Time Domain Pulses Based on Six-Port Technology - Lurz, Fabian; Lindner, Stefan; Mann, Sebastian; Linz, Sarah; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (European Microwave Conference, 2014)
This paper presents a fast responding frequency measurement system based on Six-Port technology being able to determine precisely the frequency of very short time domain pulses of 1 μs and even less in the 2.4 GHz ISM band. By using a delay line the frequency measurement can be reduced to a phase measurement that can be quickly evaluated by the Six-Port network implemented with lumped components. Measurements show that the delay line, currently realized by a SMA cable, is extremely sensitive to temperature variations even in the range of 0.1 K. Thus, a temperature compensation method based on reference measurements is proposed and final measurements show that the system can reach a calibrated and temperature compensated error of only a few parts per million (ppm).
elib2cris::1512001600,lurz2014
Keywords: Frequency measurement; Delay line; Six-Port

A Low Power 24 GHz Radar System for Occupancy Monitoring - Lurz, Fabian; Mann, Sebastian; Linz, Sarah; Lindner, Stefan; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (IEEE Radio and Wireless Symposium (RWS), 2015)
This paper presents a low power 24GHz Doppler radar system for presence detection and occupancy monitoring. It is based on a minimalistic hardware approach and is able to wirelessly sense human respiratory signals so that even non-moving persons can be detected. By intermittently measuring, the average power consumption could be significantly reduced down to e.g. 0.2mW for 20 measurements per second. Experiments verify that, due to the short wavelength, the single channel receiver limitations can be neglected when only a detection of human respiratory but no evaluation of the breathing frequency is necessary.
elib2cris::1512001600,lurz2015
Keywords: Doppler radar; low-power; occupancy sensor

A Microwave Interferometer Based Contactless Quasi-TEM Waveguide Position Encoder with Micrometer Accuracy - Mann, Sebastian; Lindner, Stefan; Lurz, Fabian; Barbon, Francesco; Linz, Sarah; Weigel, Robert; Kölpin, Alexander (IEEE MTT-S International Microwave Symposium (IMS), 2014)
Position measurement plays an important role in industrial process technology. Hereby, a waveguide based position sensor system for industrial applications is described. The proposed system features a Phase Locked Loop controlled 24 GHz signal source, an interferometric Six-Port receiver structure, a radar coupler, and a terminated quasi-TEM parallel plate waveguide structure. Furthermore, the system concept comprises a target, which can be applied both touching and contactless in the waveguide’s fringing field, reflecting a part of the transmitted wave. To obtain the target’s position information, the reflected wave is compared to a reference signal with respect to the relative phase difference. Hence, this phase shift is directly related to the position information.
elib2cris::1512001600,mann2014a
Keywords: Six-Port; position encoder; parallel plate waveguide; phase measurement

A Novel, Wide Angle, High Resolution Direction-Of-Arrival Detector - Vinci, Gabor; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (European Microwave Week (EuMW) 2011, 2011)
Direction-Of-Arrival (DOA) detection is a demanding task for a wide range of applications where high accuracy, robustness, small size, and low cost are important requirements. An innovative Six-Port based DOA detector is hereby presented. Several applications benefit from the advantages of this new interferometric detection principle. A new high resolution dual Six-Port based detector is presented featuring among the advantages provided by the interferometric principle also a wide angle of detection as well as an increased dynamic range and new digital signal processing strategies.
elib2cris::1512001600,vinci2011b
Keywords: Accuracy; Calibration; Detectors; Polynomials; Radio frequency; Receiving antennas

A Six-Port Interferometer Based Micrometer-Accuracy Displacement and Vibration Measurement Radar - Barbon, Francesco; Vinci, Gabor; Lindner, Stefan; Weigel, Robert; Kölpin, Alexander (International Microwave Symposium, 2012)
Displacement detection and vibration measure- ments are important requirements for automation and me- chanical stress diagnosis in diverse industrial environments. Laser interferometry is a widely used technique for these kinds of measurements since it features high-resolution, wide dynamic range and wide frequency response. Another advantage of the laser interferometry technique is contactless diagnosis/sensing which allows remote operations. However this technique is not suitable in harsh environments for instance with the presence of dust or fog which occur in several industrial production sites. In this paper a new contactless radar based vibration measurement technique is presented. It features an RF frontend based on a passive six- port interferometer working at 24 GHz. A dedicated signal processing unit is also presented. The proposed hardware allows to measure with a position accuracy of 0.5 µm.
elib2cris::1512001600,barbon2012a
Keywords: six-port; vibrometer; positioning; calibration; phase measurement; interferometer; radar

A Six-Port Radar System for Precise Distance Measurements and Vibration Monitoring in Industrial Environments - Vinci, Gabor; Linz, Sarah; Mann, Sebastian; Lindner, Stefan; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (Sensors and Measuring Systems; 17. ITG/GMA Symposium, 2014)
The Six-Port receiver has been subject of several investigations in the last years especially for radar applications in different areas, from accurate contactless vibration analysis, through automotive radar calibration to remote breath and heartbeat monitoring. The advantages of the Six-Port receiver such as excellent phase discrimination, trivial signal processing and low circuit complexity as well as cost, are the features that lead the radar industry to further development of this technology. A joint project involving the University of Erlangen-Nuremberg and InnoSenT GmbH (Innovative Sensor Technology), led to the development of a highly accurate, compact and versatile Six-Port radar module aiming at a reliable high-integration of all subcomponents such as antenna, Six-Port front-end, baseband circuitry and digital signal processing.
elib2cris::1512001600,vinci2014
Keywords: Six-Port; Radar; Vibration Monitoring; Industrial Environments; compact sensor

A Tank Level Sensor Based on Six-Port Technique Comprising a quasi-TEM Waveguide - Mann, Sebastian; Lindner, Stefan; Linz, Sarah; Barbon, Francesco; Talai, Armin; Weigel, Robert; Kölpin, Alexander (IEEE Topical Conference on Wireless Sensors and Sensor Networks (WiSNet), 2014)
Robust tank level monitoring is an important issue in chemical and process industry and a challenging task if high accuracy has to be reached. The proposed sensor structure consists of a quasi-TEM mode waveguide on the one hand and an interferometric Six-Port receiver structure on the other hand. The waveguide structure itself in combination with the liquid to be monitored acts as a reflection phase shifter. By superposing the reflected and the transmitted electromagnetic wave within a passive structure, the relative phase between both signals can be accurately obtained by means of the Six-Port principle. Thus, a change of the liquid level is directly related to the relative phase shift monitored by the Six-Port interferometer. In contrast to antenna based tank level sensors, the hereby presented system concept makes use of a novel waveguide structure. therefore, it is not sensitive to multi-target scenarios and multipath propagation.
elib2cris::1512001600,mann2014
Keywords: Six-Port; Interferometer; tank; level monitoring; parallel plate waveguide; RADAR; microwave measurement

A Wide-Range 77 GHz Direction of Arrival Detector with Integrated Dual Six-Port Receiver - Vinci, Gabor; Barbon, Francesco; Lämmle, Benjamin; Weigel, Robert; Kölpin, Alexander (International Microwave Symposium (IMS) 2012, 2012)
The six-port Direction Of Arrival (DOA) detector has opened a whole new set of possibilities and implementations for novel industrial sensors and radar applications. Detection ambiguity issues as well as challenging calibration techniques are still the main problems of this technology. In this paper the design of an innovative DOA detector system is presented, addressing especially solutions to the problems mentioned above. The proposed device works at 77 GHz and features an integrated Silicon-Germanium (SiGe) dual six-port receiver. Design issues are addressed as well as an overview of the DOA detector system. The highlights are high accuracy, wide range of DOA detection with no ambiguity issues, flexibility, low-complexity and low-cost.
elib2cris::1512001600,vinci2012d
Keywords: Calibration; Detectors; Microwave Circuits; Receiving Antennas; Silicon Germanium; Six-Port

Characterization In-Situ of Diode Detectors for Six-Port receivers - Barbon, Francesco; Lindner, Stefan; Mann, Sebastian; Linz, Sarah; Weigel, Robert; Kölpin, Alexander (Testmethoden und Zuverlässigkeit von Schaltungen und Systemen (TuZ), 2013)
Six-Port receivers require a precise power mea- surement thus a characterization in-situ of its power detector is necessary. The industrial working ambient requires a constant performance monitoring due to temperature drift, fabrication and component tolerances. The detectors’ performance may have some degradation, which limits the measurement accuracy. Thus, an in-situ detector characterization is necessary. In this paper, a fast and simple solution for estimating the diode detectors’ char- acteristics is presented, which is ideal for Six-Port diode power detectors. This method is fast and can be easily implemented on a microcontroller.
elib2cris::1512001600,barbon2013
Keywords: six-port; diode detector; power measurement; in-situ

Detector Design for Six-Port Radar - Linz, Sarah; Barbon, Francesco; Mann, Sebastian; Lindner, Stefan; Lurz, Fabian; Weigel, Robert; Kölpin, Alexander (CST European User Conference 2014, 2014)
The Six-port receiver has been intensively investigated in the last decades. Now, a first prototype Six-port radar sensor is available on the market. There is a great demand from the industry for the Six-port radar for applications like level metering, vibration analysis or positioning. A critical component of the Six-port radar is the detector. Good matching is necessary to avoid crosstalk between the four detectors of the Six-port and a perfect RF-short is needed to terminate the diode. In this talk, the design workflow for Schottky diode power detectors will be demonstrated. A first circuit design and simulation is done with Agilent Advanced Design System. The layout is imported into CST Microwave Studio as DXF file. By using a technology file, the 3D structure can be automatically generated. The results of both, time and frequency domain simulation, are compared with measurement results. With a circuit simulation in CST Design Studio comprising the Microwave Studio block, the manufacturer’s SPICE model is compared with measured S-Parameters of the Schottky diode. By using the diode’s measured S-Parameters and the frequency domain solver, a good agreement between simulation and measurement of the detector can be achieve
elib2cris::1512001600,linz2014
Keywords: Six-Port; Radar; Power Detector

Diode Detector Design for 61 GHz Substrate Integrated Waveguide Six-Port Radar Systems - Mann, Sebastian; Erhardt, Stefan; Lindner, Stefan; Lurz, Fabian; Linz, Sarah; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (IEEE Topical Conference on Wireless Sensors and Sensor Networks (WiSNet), 2015)
Radar sensors play a key role in today’s industrial automation. Besides high accuracy, modern radar sensors have to feature high precision as well as challenging update rates. Six-Port wave correlators enable high phase resolution at high frequencies and therefore a high accuracy in radar applications. A Schottky diode detector applied to a substrate integrated waveguide (SIW) Six-Port is presented and measured. Furthermore, a displacement measurement using the SIW structure is performed.
elib2cris::1512001600,mann2015
Keywords: Detector; interferometer; millimeter-wave; Six-Port; RADAR; phase measurement

Distance measurements and limitations based on guided wave 24 GHz dual tone Six-port radar - Lindner, Stefan; Barbon, Francesco; Linz, Sarah; Mann, Sebastian; Weigel, Robert; Kölpin, Alexander (International Journal of Microwave and Wireless Technologies, 2015)
In the following, a continuous wave radar system based on the Six-port principle will be shown for measurement tasks at enclosed systems needing micrometer accuracy as well as high update rates like tank level monitoring or hydraulic cylinder piston control. To exceed the ambiguity limit of such an interferometric system, a dual tone approach is used. The system will be presented with measurement results at 24 GHz within a WR42 waveguide to prove the feasibility of the proposed concept. Furthermore, considerations on timing will show the potential as a low-latency system, capable of high measurement data update rates, and different influences on the system performance and limitations of such a system will be discussed in comparison to alternative setups.
elib2cris::1512001600,lindner2015a

Distance Measurements Based on Guided Wave 24 GHz Dual Tone Six-Port Radar - Lindner, Stefan; Barbon, Francesco; Linz, Sarah; Mann, Sebastian; Weigel, Robert; Kölpin, Alexander (11th European Radar Conference (EuRAD), 2014)
In the following, a continuous wave (cw) radar system based on the Six-Port principle will be shown for measurement tasks at enclosed systems needing micrometer accuracy as well as high update rates like tank level monitoring or hydraulic cylinder piston control. To exceed the ambiguity limit of such an interferometric system a dual tone approach is used, extending the unambiguity range to several wavelengths. The system will be presented with measurement results at 24 GHz within a WR42 waveguide to prove the feasibility of the proposed concept.
elib2cris::1512001600,lindner2014
Keywords: distance measurement; interferometry; phase measurement; radar; Six-Port; Waveguide

Dual Tone Approach for Unambiguous Six-Port Based Interferometric Distance Measurements - Lindner, Stefan; Barbon, Francesco; Mann, Sebastian; Vinci, Gabor; Weigel, Robert; Kölpin, Alexander (IEEE International Microwave Symposium, 2013)
This publication shows an approach for absolute, unambiguous distance measurements with a Six-Port radar at 24 GHz. Such an interferometric radar has the drawback of ambiguity problem concerning phase, limiting the measuring distance to half of the used wavelength. This can be solved with the presented dual tone system using the resulting beat frequency between two tones to determine an absolute position within even several wavelengths. In the following, this system will be presented along with simulations and measurements proving the concept.
elib2cris::1512001600,lindner2013
Keywords: distance measurement; radar interferometry; absolute position determination

Evaluation of the Impact of Antenna Parameters on the Performance of Six-Port Radar - Linz, Sarah; Vinci, Gabor; Lindner, Stefan; Mann, Sebastian; Lurz, Fabian; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (IEEE-APS Topical Conference on Antennas and Propagation in Wireless Communications (APWC), 2014)
elib2cris::1512001600,linz2014a

Extended Range Distance Measurements Based on Frequency and Power Compensated Six-Port Receiver - Barbon, Francesco; Lindner, Stefan; Mann, Sebastian; Linz, Sarah; Kölpin, Alexander; Weigel, Robert (44th European Microwave Conference (EuMC), 2014)
Six-Port interferometers for distance measurement show a low cost solution able to operate in harsh environment where other solutions are not suitable. The increase of the distance range requires new calibration strategies in order to compensate the signals’ high dynamic power range. Here, an enhanced Six-Port receiver is presented having the capability of sensing the frequency of the reference signal and featuring a dynamic compensation of the power levels of the signals fed to the interferometer. These attributes allow the receiver to increase the distance detection range.
elib2cris::1512001600,barbon2014a
Keywords: Six-Port; Frequency estimation; long range; radar

Fast In-Situ Diode Detector Characterization for Six-Port Interferometer Receivers - Barbon, Francesco; Lindner, Stefan; Mann, Sebastian; Linz, Sarah; Weigel, Robert; Kölpin, Alexander (Topical Conference on Wireless Sensors and Sensor Networks (WiSNet), 2014)
Six-Port receivers require a precise power measurement of all their four output channels. However, due to temperature drift, fabrication and component tolerances the detectors' performance may have some degradation, which limits the measurement accuracy. Thus, an in-situ detector characterization is necessary. In this paper, a fast and simple solution for estimating the diode detectors' characteristics is presented, which is ideal for Six-Port diode power detectors. This method is fast and can be easily implemented on a microcontroller.
elib2cris::1512001600,barbon2014
Keywords: six-port; diode detector; power measurement; characterization; in-situ

High Accuracy Industrial Positioning Sensors Based on Six-Port Technology - Weigel, Robert; Kölpin, Alexander; Vinci, Gabor; Lindner, Stefan; Barbon, Francesco (Kleinheubacher Tagung, 2012)
elib2cris::1512001600,weigel2012c

Improved Dual Six-Port Receiver Structure for Two-Dimensional Direction of Arrival Detection Using pHEMT Power Detectors - Mann, Sebastian; Vinci, Gabor; Lindner, Stefan; Barbon, Francesco; Linz, Sarah; Weigel, Robert; Kölpin, Alexander (IEEE European Radar Conference (EuRAD), 2013)
Abstract—Two-dimensional Direction Of Arrival detection (DOA) of an arbitrary electromagnetic wave is a challenging task, especially if high accuracy has to be performed. The proposed DOA receiver is based on a phase detector using the interferometric Six-Port principle. For the proposed system an improved power detector concept using a High Electron Mobility Transistor has been developed featuring strictly square law behaviour to at least -15 dBm. Thus, the system offers a high dynamic range of more than 40 dB. The hereby presented system concept additionally has a switched delay line phase shifter for frequency estimation of the incoming electromagnetic wave. Moreover, the most important system components have been validated by measurements.
elib2cris::1512001600,mann2013
Keywords: Six-Port; Direction-Of-Arrival; Phase measurement; Power Detector; pHEMT

Initial Calibration Procedure of a Six-Port Receiver System for Complex Data Reception - Lindner, Stefan; Barbon, Francesco; Vinci, Gabor; Weigel, Robert; Kölpin, Alexander (42nd European Microwave Conference (EuMC), 2012)

Instantaneous frequency measurement based on low-cost Six-Port technology - Lindner, Stefan; Vinci, Gabor; Barbon, Francesco; Linz, Sarah; Mann, Sebastian; Weigel, Robert; Kölpin, Alexander (European Microwave Conference, 2013)
This paper describes a new approach for absolute, high accuracy and fast responding millimeter wave frequency measurement. The shown system is based on the reduction of the frequency detection to a phase measurement with a delay line and a subsequent determination of the phase. By using a Six-Port structure, this phase can be evaluated very precisely, leading to a accurate frequency detection. Another remarkable point is the fast system response, because there is neither time consuming transformation to frequency domain nor long integration time required.
elib2cris::1512001600,lindner2013a
Keywords: delay lines; frequency measurement; Detectors; millimeter wave measurement; phase measurement

I/Q Imbalance Compensation for Six-Port Interferometers in Radar Applications - Linz, Sarah; Vinci, Gabor; Lindner, Stefan; Mann, Sebastian; Lurz, Fabian; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (European Microwave Conference, 2014)
Six-port interferometers are of great interest for displacement and vibration measurements in industrial as well as medical applications. However, they show offsets as well as amplitude and phase imbalances in their differential in-phase and quadrature signals, leading to inaccuracies of the measured displacement. If a very slow moving or vibrating target has to be monitored, an additional phase shifter for calibration is needed, so that the system’s errors can be compensated. A method for calculation and compensation of errors is presented and a compact and cost-efficient implementation of a phase shifter for 24 GHz Six-port interferometers is shown.
elib2cris::1512001600,linz2014b
Keywords: Six-Port; Ellipse; IQ Imbalance; Interferometer

Promise of a Better Position - Vinci, Gabor; Lindner, Stefan; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (IEEE Microwave Magazine, 2012)
Industrial automation today is an essential technology underlying our modern society. Advanced positioning and sensor feedback tasks in automation processes often require distance displacement detection, e.g., to measure and track the movement of robots. Furthermore, the detection of mechanical stress in complex industrial machinery through an accurate vibration analysis is often a task of major interest. Therefore, high-resolution distance measurements with short- and long-range positioning are important for a large number of sensing applications and can also be used as a precondition for vibrometer applications. Several automation technologies rely on high precision positioning sensors to track linear as well as rotational movements of various machiner
elib2cris::1512001600,vinci2012g
Keywords: Automation; Displacement measurement; Feedback; Industrial plants; Machinery; Position measurement; Robot sensing systems; Sensors; Tracking; Six-Port

Selbstteststrategien für Mikrowellen-Interferometrie zur hoch-genauen industriellen Abstandsmessung - Kölpin, Alexander; Mann, Sebastian; Lindner, Stefan; Linz, Sarah; Barbon, Francesco; Weigel, Robert (Testmethoden und Zuverlässigkeit von Schaltungen und Systemen (TuZ), 2014)
elib2cris::1512001600,koelpin2014

Selftest Strategies for Microwave Interferometry for High-Precision Industrial Distance Measurements - Kölpin, Alexander; Linz, Sarah; Barbon, Francesco; Lindner, Stefan; Mann, Sebastian; Lurz, Fabian; Weigel, Robert (20th International Conference on Microwaves, Radar, and Wireless Communications (MIKON), 2014)
Microwave interferometry is a tool for precisely measuring distances or vibrations of a target in industrial applications. Distance resolutions in the range of few micrometers and measurement value update rates of several tens of kilohertz are feasible. These parameters can only be achieved, if careful compensation of non-ideal effects is conducted. In this paper the basics of Six-Port based microwave interferometry as well as selftest techniques will be presented. Exemplarily, linearization of the operating point of the diode detectors and frequency estimation of the radar signal will be shown.
elib2cris::1512001600,koelpin2014a
Keywords: Six-Port; Selftest

Signal Processing Strategies for Six-Port Based Direction of Arrival Detector Systems - Barbon, Francesco; Vinci, Gabor; Lindner, Stefan; Weigel, Robert; Kölpin, Alexander (9th International Multi-Conference on Systems, Signals and Devices (SSD), 2012)
Direction of Arrival (DOA) detection for industrial positioning is a relevant topic. Several applications make use of the six-port technology to perform phase difference based DOA measurements. The six-port receiver offers high accuracy, robustness and a low cost solution. The ability of this device to precisely measure a phase difference (hence a DOA angle) implies a correct acquisition of the signals delivered from the six-port detector as well as a correct digital signal processing. In this paper a dedicated acquisition platform for the six- port DOA detector is presented. Moreover, different software strategies to compute the DOA angle have been evaluated for an FPGA. Different types of algorithms have been implemented and compared using accuracy and throughput as references.
elib2cris::1512001600,barbon2012
Keywords: Direction-of-Arrival; Six-Port; Angle Measurement

Six-Port Based Direction Finding and Micrometer-Accuracy Displacement Detection - Vinci, Gabor; Barbon, Francesco; Lämmle, Benjamin; Weigel, Robert; Kölpin, Alexander (CST European User Group Meeting (CST EUGM) 2012, 2012)
elib2cris::1512001600,vinci2012c
Keywords: Six-Port

Six-Port-Based Direction-Of-Arrival Detection System - Vinci, Gabor; Kölpin, Alexander; Barbon, Francesco; Weigel, Robert (Asia-Pacific Microwave Conference, 2010)
Direction-Of-Arrival (DOA) detection is a fundamental procedure required by several monitoring and tracking systems for defense purposes and other security applications as well as industrial monitoring and measurement. The ability of a system to accurately determine the incident angle of an arbitrary electromagnetic wave incoming toward the observer device is an important as well as challenging task especially when low-cost and robustness are also key points for the overall tracking and detection or surveillance solution. Phase-measurement based DOA detection is commonly used in nowadays systems, but existing methods are based on traditional mixer architectures or expensive direct conversion devices increasing complexity and cost while compromising robustness. In this paper an innovative, robust and accurate technique is proposed to perform the DOA detection by means of Six-Port based Phase Measurement Detection.
elib2cris::1512001600,vinci2010a

Six-Port Based High-Resolution Smart Antenna Alignment Sensor - Vinci, Gabor; Barbon, Francesco; Lindner, Stefan; Weigel, Robert; Kölpin, Alexander (IEEE-APS Topical Conference on Antennas and Propagation in Wireless Communications, 2012)
For several wireless data transmission systems the relevance of the information is dependent on the position of the information source. Therefore, Direction Of Arrival (DOA) detection of an incoming radio frequency signal is for several applications an important task. Typical applications for which DOA detection is relevant are for instance high-accuracy indoor navigation systems and dedicated high-speed wireless data links. For accurate DOA analysis a six-port receiver front-end is proposed. Benefits of the six-port architecture are high bandwidth and low circuit complexity. A solution for simultaneous data reception and DOA detection with the enhanced six-port receiver concept is also presented.
elib2cris::1512001600,vinci2012e
Keywords: Antenna measurements; Microwave communication; Receiving antennas; Wireless sensor networks; Six-Port; Enhanced Six-Port; Smart Antenna

Six-Port Microwave Interferometer Radar for Mechanical Vibration Analysis - Vinci, Gabor; Lindner, Stefan; Mann, Sebastian; Barbon, Francesco; Linz, Sarah; Weigel, Robert; Kölpin, Alexander (European Radar Conference (EuRAD), 2013)
elib2cris::1512001600,vinci2013a

Six-Port Radar Sensor for Remote Respiration Rate and Heartbeat Vital-Sign Monitoring - Vinci, Gabor; Lindner, Stefan; Barbon, Francesco; Mann, Sebastian; Hofmann, Maximilian; Duda, Alexander; Weigel, Robert; Kölpin, Alexander (IEEE Transactions on Microwave Theory and Techniques, 2013)
A novel remote respiration and heartbeat monitoring sensor is presented. The device is a monostatic radar based on a six-port interferometer operating a continuous-wave signal at 24 GHz and a radiated power of less than 3 μW . Minor mechanical movements of the patient's body caused by the respiration as well as heartbeat can be tracked by analyzing the phase modulation of the backscattered signal by means of microwave interferometry with the six-port network. High-distance measurement accuracy in the micrometer scale as well as low system complexity are the benefits of the six-port receiver. To verify the performance of the system, different body areas have been observed by the six-port radar. The proposed system has been tested and validated by measurement results.
elib2cris::1512001600,vinci2013
Keywords: radars; radar systems; bio effects and med. appl. of RF/Microwave; biomedical applications; biomedical sensors

Six-Port Technology for Precise Geometrical Measurement Applications - an Overview - Kölpin, Alexander; Vinci, Gabor; Lindner, Stefan; Mann, Sebastian; Barbon, Francesco; Linz, Sarah; Oesterle, Florian; Weigel, Robert (European Microwave Conference (EuMC), 2013)
Instrumentation for precise geometrical measurements based on radar technology get more and more important for industrial applications. Besides distance, determining an angle or modal analysis of vibrations are key issues for automation in modern fabrication. Industrial applications put high demands on the measurement systems, not only regarding precision but also concerning operation in harsh environments and low cost implementations. In the last years Six-Port technology got more and more important for these applications. This paper will give an overview of Six-Port technique for geometrical distance measurements.
elib2cris::1512001600,koelpin2013b

Six-Port Technology for Traffic Safety - Kölpin, Alexander; Vinci, Gabor; Lämmle, Benjamin; Lindner, Stefan; Barbon, Francesco; Weigel, Robert (IEEE Microwave Magazine, 2012)
The market for driver-assistance systems for modern automobiles is rapidly growing. Formerly only provided for the luxury automotive market, these systems are nowadays more and more available for mid- and compact-class vehicles as well. This development is not only limited to the passenger car segment but is also more and more important for commercial vehicles and trucks. Some driving assistance systems have already become mandatory, e.g., the antilock breaking system (ABS). Some governments are currently thinking about requiring automatic distance control by law for heavy trucks. Automatic distance control in combination with an automatic emergency breaking system is one of the rising stars for enhancing traffic safety. Radar- based distance control mostly interacts with cruise control systems and it adapts the speed of the driver's car to the distance to the car or obstacle in front of the vehicle. Furthermore, unavoidable accidents are detected and actions for reducing the effects of the crash are automatically initiated for some systems.
elib2cris::1512001600,koelpin2012b
Keywords: six-port; AoA

The Six-Port Structure as a Precise Measurement Tool - A New Rise of an Old Concept - Kölpin, Alexander; Lindner, Stefan; Mann, Sebastian; Barbon, Francesco; Talai, Armin; Weigel, Robert (Kleinheubacher Tagung, 2013)
Six-Port Technique has been known in RF and microwave metrology since the early 1970s for vector network analysis and precise power measurements. Two decades later, the system has been proposed as a receiver for complex valued data reception. However, six-port technique has always been niche architecture, since the tremendous evolution in integrated circuit technology got more and more impact on high-end circuitry and measurement systems. But there are some special applications that can be very efficiently addressed by the six-port principle. In general, all scenarios where the interesting information is coded in signal power or can be translated in relative phase shifts are suitable for six-port systems, as this architecture offers superior phase resolution combined with low cost implementation. Furthermore, this principle can be used up to millimeter-wave frequencies and even higher. The reason is that the core functionality is realized only by passive transmission lines or waveguide structures featuring the interferometric part, and only diodes have to be used as monolithic components for the RF front-end. The information reconstruction is conducted in baseband by algorithms with very low complexity that can be run on a low power microcontroller and show only low latency of a few controller clock cycles. In this talk the newest results for applications addressed by six-port architecture for metrology will be presented. Besides very precise distance and angle measurements or vibration analysis, like heartbeat and breath rate detection, also new fields will be presented. One very promising approach is using the six-port technique for frequency analysis of a pulse-like microwave signal. Furthermore, the very first results in temperature measurements of a water basin by a six-port reflectometer will be shown.
elib2cris::1512001600,koelpin2013c
Keywords: Six-Port; Interferometer

The Six-Port Technology: A Low-Cost Concept for Precise Position Measurements - Kölpin, Alexander; Vinci, Gabor; Barbon, Francesco; Lindner, Stefan; Fischer, Georg; Weigel, Robert (9th International Multi-Conference on Systems, Signals and Devices, 2012)
Local positioning is a demanding task for industrial environments. With the help of six-port technology, a precise and easy to use concept for angle of arrival (AoA) and distance measurements will be presented in this publication. AoA resolution below 0.005° and resolving distances of 1μm for a 24 GHz six-port architecture will be shown by measurement results. Furthermore, impairments compensation issues and limitations of the technology will be discussed.
elib2cris::1512001600,koelpin2012a
Keywords: Antenna measurements; Microwave circuits; Microwave integrated circuits; Microwave measurements; Receivers; direction-of-arrival estimation; Six-Port

Two-dimensional Angle-of-arrival Analysis by One Enhanced Six-port Structure - Kölpin, Alexander; Lindner, Stefan; Mann, Sebastian; Barbon, Francesco; Linz, Sarah; Weigel, Robert (Progress In Electromagnetics Research Symposium (PIERS), 2013)
elib2cris::1512001600,koelpin2013a

Wide-Range, Dual Six-Port based Direction-Of-Arrival Detector - Vinci, Gabor; Barbon, Francesco; Lämmle, Benjamin; Weigel, Robert; Kölpin, Alexander (German Microwave Conference (GeMiC) 2012, 2012)
Direction-Of-Arrival (DOA) detection is a challenge and a demanding task for several applications among industrial sensors and automotive radar where high accuracy, robustness, and low cost are important requirements. The six-port receiver based DOA detector has opened a whole new set of possibilities and implementations due to its accurate phase measurement properties. The DOA detection angle ambiguity issue of the six-port receiver caused by phase measurement periodicity is hereby adressed. A new high resolution dual six-port based detector is presented featuring among the advantages provided by the interferometric principle also an ambiguity-free wide detection range.
elib2cris::1512001600,vinci2012b
Keywords: Calibration; Detectors; Dynamic range; Phase measurement; Radio frequency; Receivers; Schottky diodes; Six-Port